Challenging times to pharmaceutical supply chains towards sustainability: a case study application - Bravo, A.; Crespo de Carvalho, J. (International Journal of Procurement Management, 2015)
The pharmaceutical industry is one of the most high tech industries dedicated to quality, headed for the compliance fulfilment of regulatory bodies. Nevertheless, the increase of returns and recalls that is taking place, suggests the change in paradigm that is happening in this industry. Therefore, this paper is the combination of findings of previous literature reviews conducted by the authors with the application of a case study. In particular, we explore the links between pharmaceutical drugs quality, reverse logistics, and sustainability. With this approach we expect the deeper understanding on the type of returns companies receive, especially from hospital pharmacies. Consequently, it is anticipated to link both parties in the application of a quality by design risk management approach as well as reduce variability and risk of non-compliance.